Schiff base coordination flexibility toward binary cobalt and ternary zinc complex assemblies. The case of the hexadentate ligand N, N′-bis[(2-hydroxybenzilideneamino)-propyl]-piperazine. (8th January 2015) - Cretu, Carmen; Tudose, Ramona; Cseh, Liliana; Linert, Wolfgang; Halevas, Eleftherios; Hatzidimitriou, Antonios; Costisor, Otilia; Salifoglou, Athanasios
Abstract : Graphical abstract: Piperazine-based Schiff base N, N′-bis[(2-hydroxybenzilideneamino)-propyl]-piperazine, H2 L(1 ), upon reaction with Co(II)/Zn(II) afforded discrete binary-ternary [Co(L)]3 (ClO4 )3 . 4H2 O(2 ) and [Zn2 (L)(CH3 COO)2 ](3 ) assemblies. X-ray and spectroscopic studies suggest that H2 L conformational flexibility, molecular stoichiometry, and bulk constraints (a) play a crucial role in mononuclear-dinuclear M–L complex assembly, and (b) determine electronic-structural-optical properties key to development of advanced materials. Abstract: A green approach to the synthesis of N, N′-bis[(2-hydroxybenzilideneamino)-propyl]-piperazine (H2 L ) (1 ) Schiff base led to the investigation of its metal coordination reactivity under specifically set molecular stoichiometry conditions, leading to the new materials [Co(L)]3 (ClO4 )3 . 4H2 O (2 ) and [Zn2 (L)(CH3 COO)2 ] (3 ).1 –3 were characterized by elemental analysis, molar conductivity, 1 H NMR, 13 C NMR, FT-IR, UV–Vis, fluorescence, and X-ray crystallography. Crystallography reveals the conformation of the free ligand and the changes it undergoes upon coordination to Co(III) and Zn(II) ions, promoting coordination number 6 (2 ) and 5 (3 ) in the respective mononuclear and dinuclear complexes. The structural flexibility of1 coupled with the coordination requirements of the involved metal ions, under the prevailing stoichiometric conditions, shows that the strain imposed on the ligand under the reaction conditions helps it retain its original chair conformation (3 ) or assume the boat conformation (2 ). This modulatory property of1 is reflected upon the molecular assembly of the derived complexes and exemplifies its connection to the observed variable yet defined coordination mode and nuclearity of the arisen isolable species. It is in this regard that3 exhibits strong fluorescence at room temperature. Collectively, 1 –3 project the importance of conformational flexibility of organic ligand metal ionic binders in the pursuit of (a) structure-property correlations useful in the synthesis of functional materials, and (b) modulatory traits in metal ion-organic ligand interactions providing specificity in recognition processes. In this sense, 1 serves as a prototype, denoting the salient features that influence binary and ternary metal-L-(L′) assembly formation toward new materials with unique structural and photoactive properties.